2013
DOI: 10.1002/jcp.24413
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone increases GLUT4‐dependent glucose uptake in cardiomyocytes

Abstract: Testosterone exerts important effects in the heart. Cardiomyocytes are target cells for androgens, and testosterone induces rapid effects via Ca(2+) release and protein kinase activation and long-term effects via cardiomyocyte differentiation and hypertrophy. Furthermore, it stimulates metabolic effects such as increasing glucose uptake in different tissues. Cardiomyocytes preferentially consume fatty acids for ATP production, but under particular circumstances, glucose uptake is increased to optimize energy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 49 publications
2
45
0
Order By: Relevance
“…Recently, Wilson et al [19] reported that testosterone (100 nM) stimulates glucose uptake through GLUT4 and activates the CaMKII/AMPK signaling pathway in cultured cardiomyocytes. The results of Western blot analysis with anti-phospho-CaMKI antibodies and a time-course examination of the CaMKII and AMPK phosphorylation in this study suggest that testosterone-BSA stimulates GLUT4-dependent glucose uptake through activation of the Ca 2?…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, Wilson et al [19] reported that testosterone (100 nM) stimulates glucose uptake through GLUT4 and activates the CaMKII/AMPK signaling pathway in cultured cardiomyocytes. The results of Western blot analysis with anti-phospho-CaMKI antibodies and a time-course examination of the CaMKII and AMPK phosphorylation in this study suggest that testosterone-BSA stimulates GLUT4-dependent glucose uptake through activation of the Ca 2?…”
Section: Discussionmentioning
confidence: 98%
“…Clinical and experimental studies have shown that low serum testosterone concentrations are linked to metabolic disorders, including metabolic syndrome, type 2 diabetes, and hepatic steatosis [11][12][13][14][15][16][17]. In addition, testosterone has been reported to increase GLUT4-dependent glucose uptake in skeletal muscle cells and cardiomyocytes [18,19]. However, studies on glucose uptake occurring in response to testosterone stimulation in adipocytes are currently not available.…”
Section: Introductionmentioning
confidence: 95%
“…T has been found to increase cardiomyocyte glucose uptake by augmenting GLUT4 translocation56 and although an increase in GLUT 4 protein expression was not seen in the left ventricle under basal condition, the increase in expression of insulin signaling proteins including IRS-1, PI3K and AKT is suggestive of increase in glucose metabolism within the left ventricle. Free fatty acids are the primary fuel for energy production in cardiac tissue but during fetal life and during times of stress, the heart does revert to glucose as its primary source of fuel57.…”
Section: Discussionmentioning
confidence: 92%
“…Recombinant TNF-α (10 ng/mL), IL-1ß (50 ng/mL), IFN-γ (10 ng/mL), or Ang-II (100 ng/mL) were added to the cell culture medium, and cells were incubated for 24 h before RNA expression of FNDC5 or PGC-1α was analysed in the myotubes by reverse transcription (RT)-PCR. The effects of PD98059 (50 µmol/L; Calbiochem, La Jolla, CA, USA), a specific inhibitor of p42/44 mitogen-activated protein kinase (MAPK),18 SB203580 (10 µmol/L; Calbiochem, La Jolla, Ca, USA), a specific p38-MAPK inhibitor,19 chelerythrine (2 µmol/L; Sigma, Taufkirchen, Germany), a specific protein kinase C (PKC) inhibitor,20 SP600125 (20 µmol/L; Sigma, Taufkirchen, Germany), a specific c-Jun N-terminal kinase inhibitor,21 Akt inhibitor VIII (20 µmol/L; Sigma Taufkirchen, Germany),22 and nifuroxazide (10 µmol/L; Santa Cruz, Heidelberg, Germany), a specific signal transducer and activator of transcription 3 (STAT-3) inihibitor23 on FNDC5 expression, were tested by pre-incubating cells for 2 h before the addition of inflammatory cytokines.…”
Section: Methodsmentioning
confidence: 99%